A review of the door to needle time for administration of fibrinolytics in acute myocardial infarction in Cape Town - Maharaj, Roshen Chathram (Division of Emergency Medicine, 2015)
The aim of this study is to determine the current door to needle time for administration of fibrinolytics in acute myocardial infarction in Emergency Centres in the Cape Metropole. This study will also aim to identify the factors contributing to the delay.